2018
DOI: 10.1111/imb.12541
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal control and target genes of ftz‐f1 expression in the honeybee Apis mellifera: a positive loop linking juvenile hormone, ftz‐f1, and vitellogenin

Abstract: Ftz‐f1 is an orphan member of the nuclear hormone receptor superfamily. A 20‐hydroxyecdysone pulse allows ftz‐f1 gene expression, which then regulates the activity of downstream genes involved in major developmental progression events. In honeybees, the expression of genes like vitellogenin (vg), prophenoloxidase and juvenile hormone‐esterase during late pharate‐adult development is known to be hormonally controlled in both queens and workers by increasing juvenile hormone (JH) titres in the presence of declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 72 publications
4
30
0
Order By: Relevance
“…This means that there is the potential for diversified types of signaling and response in the eusocial insect colony, as well as elaboration of the molecular mechanisms underlying the response to stimuli. Functional genomic approaches that simultaneously consider multiple socially-interacting individuals, e.g., based on sequencing a time series of interacting nurse workers and larvae 152 shows that even the most fundamentally important conserved genes have distinctly different expression patterns in eusocial insects as compared to solitary insects, as well as expression variation between related eusocial species and among nestmates 31,[158][159][160] . The convention has been to act as if use of an ortholog constitutes conservation, but already for key cases such as PKG we know the same locus can be associated with a trait (e.g.…”
Section: Predictions For Glandsmentioning
confidence: 99%
“…This means that there is the potential for diversified types of signaling and response in the eusocial insect colony, as well as elaboration of the molecular mechanisms underlying the response to stimuli. Functional genomic approaches that simultaneously consider multiple socially-interacting individuals, e.g., based on sequencing a time series of interacting nurse workers and larvae 152 shows that even the most fundamentally important conserved genes have distinctly different expression patterns in eusocial insects as compared to solitary insects, as well as expression variation between related eusocial species and among nestmates 31,[158][159][160] . The convention has been to act as if use of an ortholog constitutes conservation, but already for key cases such as PKG we know the same locus can be associated with a trait (e.g.…”
Section: Predictions For Glandsmentioning
confidence: 99%
“…For example, Liu et al [45] found that knockdown of FTZ-F1 in final-instar larvae caused significant impairment of pupation in L. decemlineata [45]. In A. mellifera, cuticle pigmentation and wing formation during developmental processes were severely impaired by downregulation of FTZ-F1 [25]. Recently, Li et al [27] reported that FTZ-F1 mediates the expression of CYP6BG1, conferring resistance to chlorantraniliprole in P. xylostella.…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 ] found that knockdown of FTZ-F1 in final-instar larvae caused significant impairment of pupation in L. decemlineata [ 45 ]. In A. mellifera , cuticle pigmentation and wing formation during developmental processes were severely impaired by downregulation of FTZ-F1 [ 25 ]. Recently, Li et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad and Ftz-F1 mediate the transcription-dependent effects of JH on cell physiology during development in other insect species (Bonneton and Laudet, 2012) and (at least in the case of Ftz-F1) in pharate adult bees (Mello et al, 2018). JH plays a strong role in regulating honey bee behavioral maturation (Robinson, 1992).…”
Section: Jh Analog Administrationmentioning
confidence: 99%